EFEKTIVITAS PENGGUNAAN DANA DESA DALAM PROGRAM KEBUN KOLEKTIF DI DESA LATOMPE KECAMATAN LAWA KABUPATEN MUNA BARAT - Ardian Oktafiani; Musadar Musadar; La Ode Kasno Arif (Universitas Halu Oleo, 2023)
This study aims to assess the effectiveness of village funds in the collective garden program in Latompe Village, Lawa Sub-district, West Muna Regency. The study population consisted of all farmers involved in the collective garden program, totaling 38 individuals. The sample was determined using the census method, resulting in a sample size of 38 individuals. The research data were collected through observation, interviews, and documentation using questionnaires as research instruments. The use of village funds was determined through quantitative descriptive analysis with a Likert scale, and the effectiveness formula was used to determine the level of effectiveness of the use of village funds in the collective garden program. The study found that the use of village funds in the collective garden program in Latompe Village, Lawa District was generally effective, with a 61.94% success rate based on target parameters, benefit suitability, and expectations. The language used is clear, concise, and objective, with no biased or ornamental language. The sentence structure is simple and the technical terms are explained when first used. The grammar, spelling, and punctuation are correct. No changes in content were made. The effectiveness of the collective garden program's use of village funds is moderately satisfactory in terms of the parameters of period and timeliness.